Corporate Financial and Strategic Determinants of Firm Value: Evidence from Indonesian Food and Beverage Companies - Komala Ardiyani; Januara Catur Pramudita (Universitas Pekalongan, 2026)
Corporate financial and strategic decisions play a fundamental role in shaping firm value by influencing investors' perceptions of corporate sustainability and future growth prospects. This study examines how corporate financial and strategic determinants affect the firm value of Indonesian food and beverage companies listed on the Indonesia Stock Exchange during the 2018–2022 period. The financial determinants consist of financing decisions and dividend policy, while the strategic determinants include diversification strategy, operational efficiency, and innovation. This study adopts a quantitative explanatory approach using secondary data obtained from audited annual reports and financial statements. Purposive sampling generated 135 firm-year observations from 27 companies. Firm value is measured using Price-to-Book Value (PBV), while the proposed hypotheses are tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS 8.0. The findings indicate that financing decisions, innovation, and dividend policy positively influence firm value, whereas diversification strategy and operational efficiency do not exhibit significant effects. These results suggest that investors assign greater importance to firms' financial policies, innovation capability, and dividend distribution than to diversification initiatives or asset utilization efficiency when evaluating corporate value. This study enriches the literature on corporate finance and strategic management by providing empirical evidence from Indonesia's food and beverage industry and offers practical implications for managers in designing policies that enhance shareholder value.